The Influence of Content Marketing, Online Reviews, and Customer Ratings on Purchase Intention with Customer Trust as a Moderating Factor - Heppy Agustiana Vidyastuti; Fatahillah Syahrul (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
This study investigates the influence of content marketing, online customer reviews, and customer ratings on consumers’ purchase intentions, with customer trust positioned as a moderating variable. The main contribution of this research lies in its integrated analytical framework, which simultaneously examines three key digital marketing cues within a trust-based mechanism. Moreover, this study focuses on Indonesian marketplace users, a context that remains underexplored in the existing literature, as previous studies have predominantly examined these variables separately or in different market settings. Using a quantitative research design, data were collected from 322 active marketplace users in West Java aged 17 years and above. The analysis was conducted using Structural Equation Modeling with SmartPLS 4 to evaluate both direct and indirect relationships among the constructs. The empirical findings indicate that content marketing has a significant positive effect on purchase intention; however, it does not significantly influence customer trust. In contrast, customer ratings and online customer reviews are found to have a strong and significant effect on customer trust, which subsequently enhances purchase intention. Further analysis reveals that customer trust mediates the relationship between customer ratings and purchase intention, indicating a significant indirect effect. Conversely, the indirect effects of content marketing and online customer reviews on purchase intention through customer trust are not supported. These findings suggest that trust functions selectively within digital purchasing mechanisms, rather than uniformly moderating all marketing stimuli. From a theoretical perspective, this study enriches the digital consumer behavior literature by highlighting the differentiated role of trust in shaping online purchase decisions. Practically, the results underscore the importance for marketplace platforms and online sellers to prioritize trust-building strategies, particularly through transparent rating systems and credible customer reviews, in order to effectively enhance consumers’ purchase intentions.